Carpet Beetles - P.G. Koehler (EDIS)
This document provides an overview of carpet beetles, including their biology, life cycle, and the damage they cause to fabrics and furnishings. Carpet beetles feed on natural animal fibers and can infest homes from bird, rodent, and insect nests. The document details the life stages of various carpet beetle species and emphasizes the importance of good housekeeping and proper storage to prevent infestations. Control methods include regular cleaning, inspection, and the use of insecticides and nonchemical treatments like cedar products and cold storage. Publication date: August 1991.